Relationship Long Time Storage of Trunk Fish (Euthnymus Affinis) Smoke With The Presence Of Staphylococcus Aureus Bacteria At Bobotsari Traditional Market - Romadhon, Zakiyatudin Anduko; Mulyanto, Arif; Mujahid, Ikhsan; Widodo, Oei Stefani Yuanita (Poltekkes Kemenkes Mataram, 2023)
Fresh fish can experience spoilage due to the activity of enzymes and microorganisms contained in the body of the fish itself due to the oxidation process in body fat by air. The body of the fish contains water which is quite high, namely 60-80% and has a pH of 7.2 so that it can be a good medium for the growth of putrefactive bacteria. Preservation methods are carried out to reduce the presence of spoilage alternatif preservation can be done, among others, by salting, cooling, drying, and smoking. Excess fumigation contains phenol which can function as an anti-microbial so that microbes will die and not develop. The purpose of this study was to determine the relationship between long storage of smoked tuna (Euthynmus affinis) and the presence of Staphylococcus aureus bacteria. The sample in this study were 12 samples of smoked cob fish which were sold in the traditional markets of the ballpark and the sampling technique used was random sampling. This type of research was experimentally analyzed using the Kruskall Wallis test. The results of the study of 12 samples of tuna that contained Staphylococcus aureus bacteria concluded that there was a relationship between storage duration of smoked tuna (Euthynmus affinis) and the presence of Staphylococcus aureus bacteria.